Kajian Keanekaragaman Artropoda pada Lahan Padi Sawah Tanpa Pestisida dan Manfaatnya dalam Pengendalian Hama Terpadu - Eddy Mahrub (Universitas Gadjah Mada, 1999)
The objectives of the research are to study the diversity and abundance of arthropods, and to study the foodweb chain composition in the ricefield ecosystem without application of chemical pesticide. This research has been done in the ricefield at Klaten district, with IR64 rice cultivar. The observation was started when the plant was 7 days old after transplanting, with an interval of 8 days until one week before harvesting, to collect the arthropods samples. Three plots and 50 hills per plot were sampled weekly. Arthropods from each hill were collected by using insect sucking apparatus. The data was analyzed following Cheng method to study the arthropod index diversity and its abundance. The results showed that in the rice ecosystem there were four groups o arthropod consisted of pest (21.19%); predator (26.09%); parasitoid (0.42%), and neutral insect (52.30%). Data of the pest population was very low in free from chemical pesticide application, plot while population of neutral insect was very high. The high population of neutral insect was very useful and functionary as alternate prey for predator and parasitoid when the pest population was very low. The diversity index (H’) of arthropods during the rice growing period in the first to the fourth week increased from 1.38 to 2.37, but during the fifth to the eleventh week the diversity was about constantly low. The diversity index decreased linearly with the rice growth stage, but as the plant got older the population of arthropods decreased because the habitat became unfavourable. It might cause the diversity index and the abundance decreased. Some of the arthropods moved to new area to find the most suitable habitat. There was a foodweb chain in the rice ecosystem consisted of arthropods complex including the natural enemies and which were neutral insects. It indicated a good balanced condition between pest and natural enemies more profitable when no chemical pesticide intervention was applied in the ecosystem.